A Randomized Controlled Trial Evaluating the Efficacy of Oral Sucrose in Infants 1 to 3 Months Old Needing Intravenous Cannulation. (7th September 2016) - Desjardins, Marie Pier; Gaucher, Nathalie; Curtis, Sarah; LeMay, Sylvie; Lebel, Denis; Gouin, Serge
Abstract: Objectives: The objective was to compare the efficacy of an oral sucrose versus placebo in reducing pain in infants 1 to 3 months of age during intravenous (IV) cannulation in the emergency department. Methods: A randomized, double‐blind, placebo clinical trial was conducted. Participants were randomly allocated to receive 2 mL of an oral 88% sucrose solution or 2 mL of a placebo solution orally. The outcome measure were mean difference in pain score at 1 minute post–IV cannulation assessed by the Face, Legs, Activity, Cry, and Consolability Pain Scale (FLACC) and the Neonatal Infant Pain Scale (NIPS), crying time, and variations in heart rate. Results: Eighty‐seven participants completed the study, 45 in the sucrose group and 42 in the placebo group. There was no statistical difference in variations in both the FLACC score (p = 0.49) and the NIPS score (p = 0.36) between the two groups as per the Mann‐Whitney U‐test. With the same test, median crying times following IV cannulation were statistically significantly different between both groups (17 seconds in the sucrose group vs. 41 seconds in the placebo group, p = 0.04). Mean changes in heart rate 1 minute after IV cannulation were similar in both groups (16 ± 4 beats/min for sucrose vs. 18 ± 4 beats/min for placebo, p = 0.74). Side effects were similar for both groups and no adverse events were reported. Conclusions: Administration of an oral sucrose solution in infants 1 to 3 months of age during IV cannulation did not lead to statistically significant changes in pain scores. However, the cry time was significantly reduced.